The Culinary Space: Food as a Narrative Tool in Agatha Christie’s Detective Novels - Chakravarty, Prerana (SARE: Southeast Asian Review of English, 2023)
Kevin Burton Smith in his article ‘Murder on the Menu’ (2010), comments, “right from the start there’s been a curious link between food (and drink) and crime fiction.” Despite the fact that culinary mystery novels arose as a subgenre of crime fiction in the late twentieth century, food has always been a part of crime fiction, and has played an important role in the early stories of Sherlock Holmes and Edgar Allan Poe. Food is frequently depicted as a source of stability and order in crime novels, establishing verisimilitude, creating a genuine world, a world as we know it. Agatha Christie, too, has included significant reference to food, eating habits and food rituals throughout her detective stories, using it as a tool to create a feminine and domestic space. This paper will analyse how Christie has used the depiction of food as a tool to further the narrative, portraying it in her novels as a calming ritual and a clue to the murder. However, food in Christie’s stories can also gain a more sinister undertone, and this paper will also analyse this, focusing on how Christie transforms food into a murder weapon itself, as a bad omen indicating events, thereby, blending reality with the storyline and lending vivacity to her characters and her plots.